Abrasive wear resistance optimization of three different carbide coatings by the Taguchi method - Gur, Ali Kaya; Kaya, Sinan (Carl Hanser Verlag, 2017)
In this study, FeCrC, SiC and B4C powders were alloyed on the surface of AISI 430 ferritic stainless steel by plasma arc welding. The mass losses of the abrasive wear of the AISI 430 substrate were examined under the loads of 6, 10 and 16 N and in the distances of 10, 20 and 30 m by using Taguchi design method. The results of abrasive wear test were optimized by the minimum optimal control characteristics of the Taguchi procedure and the results were analyzed by using graphical methods. The Taguchi procedure is an important approach to achieve high quality without increasing the cost during the optimization of process parameters. The orthogonal planes of maximum effects of the controllable process parameters and minimum effects of uncontrollable process parameters were employed in the Taguchi method.
Keywords: PTA surface coating; B4C; SiC; FeCrC